METODE TUTOR SEBAYA DALAM MENINGKATKAN HASIL BELAJAR FISIKA MATERI GERAK LURUS - Masruri, Ahmad (Jurnal Teladan: Jurnal Ilmu Pendidikan dan Pembelajaran, 2021)
This study aims to improve learning outcomes in straight motion physics subjects through the application of the peer tutoring method. This research method uses a classroom action research approach to solve the problem of low learning outcomes physics material straight motion using a spiral reflection system from Kemmis & Taggard. Data collection techniques are carried out by observation and tests with research subjects of class X MIPA-A SMA Negeri 2 Tuban in the academic year 2019/2020 odd semester totaling 36 students. This research was conducted in 2 cycles with the conclusion that the application of the peer tutoring method can improve learning outcomes in physics subjects in class X IPA-A at SMA Negeri 2 Tuban with the percentage of completeness of classical learning outcomes 86.11% and an average value of 84.44.